Analytical assessment process of e-learning domain research between 1980 and 2014 - Jalali, S. M. J. (2017)
Applying some methods to reduce the time and expenditures of training is inevitable in existing circumstances. Many educational organizations have realized the importance of Electronic Learning (E-learning) and tried to use this approach in leveraging their academic classes. As research in E-learning domain has become one of the most important and interesting subjects, observation in emerging and fading trends of E-learning is a need for the scholars and industry professionals who are interested to study and work in the field. This paper has triggered the investigation and depicting of scientific trends in E-learning by using two scientometric methods named burst detection and clustering analysis. By applying two mentioned methods, the hot topics were identified in the field of E-learning.